Answer:
(2,-1)
divide both sides of the first equation by 2 to get y by itself. this gets you y=x/2-2
then plug that into the other equation:
4x+3(x/2-2)=5
SImplify that to get:
4x+3x/2-6=5
Add 6 to both sides:
4x+3x/2=11
give 4x a denominator of 2 as well:
8x/2+3x/2=11
add them:
11x/2=11
multiply both sides by 2/11 to get:
x=22/11 which simplifies to x=2
plug x into first equation:
2y=(2)-4
simplify:
2y=-2
divide both sides by 2 to get:
y=-2/2 which is the same as -1
x=2
y=-1
answer: (2,-1)
I hope this helps